The return to capital in Ghana - Christopher Udry; Santosh Anagol (Yale University, Economic Growth Center, 2006)
We show that the real return to capital in Ghana's informal sector is high. For farmers, we find annual returns ranging from 205-350% in the new technology of pineapple cultivation, and 30-50% in well-established food crop cultivation. We also examine the relative prices of durable goods of varying durability, and estimate a lower bound to the opportunity cost of capital of 60%.
Keywords: O12; O16; D24; 330; Capital; durable goods; credit markets